2020
DOI: 10.1039/d0cy00040j
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances and prospects of inkjet printing in heterogeneous catalysis

Abstract: This review provides an insight into inkjet printing technology in the context of heterogeneous catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 145 publications
(191 reference statements)
1
26
0
Order By: Relevance
“…Previous best practices suggested that the ink should display a stable Newtonian fluid with viscosity and surface tension in the range of 1–20 mPa s and 25–50 mN m −1 , respectively for inkjet printing. [ 34 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous best practices suggested that the ink should display a stable Newtonian fluid with viscosity and surface tension in the range of 1–20 mPa s and 25–50 mN m −1 , respectively for inkjet printing. [ 34 ]…”
Section: Resultsmentioning
confidence: 99%
“…Previous best practices suggested that the ink should display a stable Newtonian fluid with viscosity and surface tension in the range of 1-20 mPa s and 25-50 mN m −1 , respectively for inkjet printing. [34] Figure 5a shows the viscosity curve as a function of shear rate for MWCNTs inks with GA and PVP surfactants. Both inks met the printing requirements by recording a viscosity range of 1-13 mPa s at a shear rate of 10 to 1000 s −1 .…”
Section: Rheological Assessment Of Mwcnts Inksmentioning
confidence: 99%
“…To avoid operating at high temperature, thermal DOD printers work well with low boiling point solvents, such as water or short‐chain alcohols. [ 37 ] In the piezoelectric DOD mode printing, a piezoelectric actuator is used to generate the pressure pulse by applying mechanical force to the ink chamber. Printable ink is thus purged out from the chamber by the formed pressure pulse and deposited on a substrate.…”
Section: Inkjet Printing Technologymentioning
confidence: 99%
“…The suggested surface tension range in DOD mode is generally between 20–50 mN m −1 . [ 37,39 ] Too high surface tension will hinder the formation of ink droplets, and too low surface tension will cause air inhalation, thus reducing the quality of printing. [ 49 ] To avoid nozzle clogging and damage, the particle size of the functional materials must be strictly controlled, which is required to be less than 1/50 of the nozzle diameter.…”
Section: Inkjet Printing Technologymentioning
confidence: 99%
“…In contrast, inkjet printing is being widely adopted to fabricate electronic devices in a digital noncontact mode that allows for printing on large areas and on a variety of substrates with low wastage of materials, thus, rendering it cost effective, facile, and scalable. In the case of all-solid-state batteries (ASSB), electrolyte/electrode interfaces are very critical toward the functionalities, and to achieve the desired electrolyte/electrode interface characteristics, either high pressure or a combination of high pressure and temperature needs to be applied. Therefore, inkjet printing, which can be performed at relatively low temperatures and ambient pressure, can play a major role in the fabrication of ASSBs by printing both the solid electrolyte and the active electrode (especially for thin ASSBs and micro ASSBs), thus helping address the problems associated with the interfaces and degradation during high-temperature processing. Furthermore, additive manufacturing techniques, such as direct ink writing and stereolithography, have been used to develop electrodes for LIBs. , The inkjet-printing method has been successfully used to fabricate SnO 2 , Li 4 TiO 12 , and Si-based thin films as negative electrodes for flexible LIBs .…”
Section: Introductionmentioning
confidence: 99%